2015
DOI: 10.1007/s10973-015-4944-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis mechanism of a β-O-4 type lignin dimer model compound

Abstract: To help understand the pyrolysis mechanism of lignin, a non-phenolic lignin dimer model compound with b-O-4 linkage, namely 1-methoxy-2-(4-methoxyphenethoxy) benzene, was prepared. Its pyrolysis mechanism was investigated by density functional theory calculations and confirmed by the analytical pyrolysis-gas chromatography/mass spectrometry experiments. Possible pyrolytic pathways were proposed and analyzed based on three initial pyrolysis mechanisms of the model compound, including the C b -O homolytic mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Pyrolysis of PPE may follow mechanisms 1, 2 and 11 to decompose, and their competitiveness is in the order of mechanism 2 > mechanism 1 > mechanism 11. α-OH-PPE may undergo pyrolysis reactions through mechanisms 1, 2, 4, 5, 6 and 11, and their competitiveness follows the order of mechanism 2 > mechanism 1 > mechanism 4 > mechanism 11 > mechanism 5 > mechanism 6. β-CH 2 OH-PPE may follow five pyrolysis mechanisms to decompose, whose competitiveness order is mechanism 2 > mechanism 1 > mechanism 7 > mechanism 8 > mechanism 11. o -CH 3 O-PPE also has five possible pyrolysis mehanisms with the competitiveness order of mechanism 2 > mechanism 3 > mechanism 1 > mechanism 10 > mechanism 11. It is important to note that the major pyrolytic products of the four model compounds obtained through DFT calculations shown in the Supplementary Materials agree well with the experimental results [ 18 , 19 , 29 , 31 ], which futher confirms the validity of the pyrolysis model. Based on the results, a similar conclusion can be drawn that most of the concerted mechanisms are prior to homolytic mechanisms, except for mechanism 6.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Pyrolysis of PPE may follow mechanisms 1, 2 and 11 to decompose, and their competitiveness is in the order of mechanism 2 > mechanism 1 > mechanism 11. α-OH-PPE may undergo pyrolysis reactions through mechanisms 1, 2, 4, 5, 6 and 11, and their competitiveness follows the order of mechanism 2 > mechanism 1 > mechanism 4 > mechanism 11 > mechanism 5 > mechanism 6. β-CH 2 OH-PPE may follow five pyrolysis mechanisms to decompose, whose competitiveness order is mechanism 2 > mechanism 1 > mechanism 7 > mechanism 8 > mechanism 11. o -CH 3 O-PPE also has five possible pyrolysis mehanisms with the competitiveness order of mechanism 2 > mechanism 3 > mechanism 1 > mechanism 10 > mechanism 11. It is important to note that the major pyrolytic products of the four model compounds obtained through DFT calculations shown in the Supplementary Materials agree well with the experimental results [ 18 , 19 , 29 , 31 ], which futher confirms the validity of the pyrolysis model. Based on the results, a similar conclusion can be drawn that most of the concerted mechanisms are prior to homolytic mechanisms, except for mechanism 6.…”
Section: Resultssupporting
confidence: 80%
“…Due to the complex structure of natural lignin, lignin-based model compounds are widely used to investigate the pyrolysis mechanism of lignin. Considering that the β- O -4 linkage is dominant, accounting for about half of the linkages in lignin, β- O -4 type lignin dimer model compounds are typically selected for theoretical studies [ 13 , 17 , 18 , 19 ]. Previous research has investigated the pyrolysis mechanism of various β- O -4 type lignin dimer model compounds containing different functional groups on the alkyl side chain and aromatic ring [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, lignin structure is expected to be reasonably preserved during CBP, which has important implications for β-O-4 content and S/G ratio. Several recent studies into pyrolysis and its product heterogeneity employed β-O-4 model compounds (443)(444)(445)(446)(447), which indicate that these bonds are The S/G ratios also exhibited relatively minor changes, meaning that CBP did not drastically alter lignin. The low S/G ratio lignin natural variant would be a competitive starting material for carbon fibers, because low S/G ratios have been associated with higher glass transition temperatures, greater cross-linking, and higher molecular weights, which promotes its function in carbon fibers (452).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Robichoud et al 21 carried out a pyrolysis study on dimethoxybenzene model compound and observed 2-hydroxybenzaldehyde as one of the products. Similarly, Zhang et al 24 also carried out pyrolysis study on the lignin dimer model compound and reported 2-hydroxybenzaldehyde as one of the products along with guaiacol, catechol, and others. Since 2-hydroxybenzaldehyde comprises two oxy-functionals, namely, hydroxyl and aldehyde groups, it still needs to be upgraded to achieve the nonoxygenated component.…”
Section: Introductionmentioning
confidence: 97%